2020
DOI: 10.1055/a-1254-5182
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sedation on the Performance Indicator of Colonic Intubation

Abstract: Background: Performance Indicator of Colonic Intubation (PICI) has been introduced as new measure of high-quality colonic intubation. Adequate PICI was defined as cecal intubation without significant discomfort and use of minimal sedation. In a UK national audit, adequate PICI was achieved in 54.1% of colonoscopies and associated with higher polyp detection rates. In this study, achievement of PICI was assessed within the Dutch colorectal cancer (CRC) screening program and the association between PICI and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…To our knowledge, this is the largest study to date specifically evaluating the effects of sedation in ADR among outpatient colonoscopies. In previous studies, it is reported that sedation can improve patient comfort and satisfaction [12,16,[23][24][25]. However, the overall quality indicators, the findings (about impact of sedation) are controversial, both in terms of demonstrating an increase and in terms of demonstrating similarity.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the largest study to date specifically evaluating the effects of sedation in ADR among outpatient colonoscopies. In previous studies, it is reported that sedation can improve patient comfort and satisfaction [12,16,[23][24][25]. However, the overall quality indicators, the findings (about impact of sedation) are controversial, both in terms of demonstrating an increase and in terms of demonstrating similarity.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the largest study to date speci cally evaluating the effects of sedation in PDR and ADR among outpatient colonoscopies. In previous studies, its' reported that sedation can improve patient comfort and satisfaction [12][13][14][15][16] . However, the overall quality indicators, the ndings are controversial, both in terms of demonstrating an increase and in terms of demonstrating similarity.…”
Section: Discussionmentioning
confidence: 99%
“…Cecal intubation rate was higher when colonoscopies were performed with sedation which is in accordance with the data from the literature. There is a new measure of quality in colonoscopy that is being studied, called Performance Indicator of Colonic Intubation (PICI), which is defined as the rate of cecal intubation without significant discomfort and use of minimal sedation ( Nass et al, 2021 ). The study of this indicator shows that there is an interest in reducing the amount of sedation during colonoscopy, or in performing as many examinations as possible without sedation, while maintaining the comfort of the patient and the quality of the examination.…”
Section: Discussionmentioning
confidence: 99%